The Influence of the Work Environment on the Mental and Physical Health of the Employees - Satya, Vincentia Vania; Satya, Victoria Jane (Oshada, 2025)
The work environment is an important factor that can affect the mental and physical health of employees. This study aims to analyze how various aspects of the work environment, including work pressure, social support, as well as the physical conditions of the workplace, contribute to the well-being of employees. Using a qualitative phenomenology-based approach, this study explores the subjective experiences of employees through in-depth interviews, focus group discussions (FGDs), and direct observation in the workplace. Research participants were selected by purposive sampling with the criteria of having worked for at least one year in various positions and departments. The results showed that high workload and lack of social support contribute to stress and fatigue, while the physical condition of the workplace that is not ergonomic increases the risk of musculoskeletal disorders. Conversely, a supportive work environment, such as work flexibility and good social relationships, can improve employee well-being. These findings indicate that companies need to improve work policies and practices to create a healthier and more productive environment. By understanding the factors that affect the mental and physical health of employees, organizations can develop more effective strategies in improving the well-being and performance of their workforce.